Literature Review: Gizi Antenatal terhadap Kejadian Stunting - Terry Y.R. Pristya; Azizah M Fitri; Widayani Wahyuningtyas (Jurnal Kesehatan, 2021)
The period of pregnancy is one of the two causes of stunting. Nutritional intake during pregnancy is necessary for the growth and development of the organs that are being formed. The purpose of this literature review is to analyze the factors that cause stunting originating from pregnancy in terms of antenatal nutrition. This study is a literature review which is a primary data research article on antenatal nutrition on stunting conducted in Indonesia. The data source used is in the form of journal publications with research locations in Indonesia. Search for articles using a search engine with databases on Google Scholar and Garuda Portal. Keywords in English and Indonesian, include nutrition, pregnant women, stunting, nutrition, antenatal, pregnancy. Obtained 5 articles that fit the inclusion criteria then synthesized the data. The results showed that the factors causing stunting originating from the period of pregnancy in terms of antenatal nutrition consisted of protein, energy, and iron. One of the actions that can be taken to avoid deficiency of these nutritional elements during pregnancy is by providing education to pregnant women to pay attention to nutritional intake during pregnancy.